2016
DOI: 10.3109/0886022x.2015.1128839
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hypertension among an ethnic group in Sudan: implications for prevention

Abstract: Objective Hypertension is an emerging non-communicable disease in developing countries. Due to its silent nature and serious complications, active screening is essential in order to prevent complications. For instance, premature mortality from cardiovascular diseases could be prevented by the effective control of hypertension. The aim of this study was to determine the prevalence of undiagnosed hypertension among Nuba ethnic group living in Atbara city, north Sudan and to identify the associated risk factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 18 publications
4
15
0
7
Order By: Relevance
“…While in rural population, the prevalence was estimated to be 15-38% in Sudan [ 23 , 24 ]. Importantly, the prevalence of hypertension in Nubia ethnic population in South of Sudan living in the North of Sudan was estimated to be around 50% [ 25 ]. Importantly, several studies indicated that DM emerged as a strikingly common correlate to hypertension [ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While in rural population, the prevalence was estimated to be 15-38% in Sudan [ 23 , 24 ]. Importantly, the prevalence of hypertension in Nubia ethnic population in South of Sudan living in the North of Sudan was estimated to be around 50% [ 25 ]. Importantly, several studies indicated that DM emerged as a strikingly common correlate to hypertension [ 26 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, aquellos que abusaban del alcohol y consumían frutas ≤4 veces/semana mostraron mayor probabilidad de HTA y/o diabetes no diagnosticada. En diferentes estudios realizados en población hipertensa las mujeres mostraron menor probabilidad de HTA no diagnosticada que los hombres 3,17 . Sin embargo, en diabéticos no se observó asociación significativa entre patología y sexo 4,19 .…”
Section: Discussionunclassified
“…La asociación entre consumo de alcohol e HTA o diabetes sin diagnosticar se ha documentado en diversos estudios 3,16,17,19,20 . El alcohol ha sido identificado como un FR de problemas cardiovasculares, es más, el elevado consumo de éste se ha asociado con HTA 3 . En los individuos de Cambé se encontró una asociación entre el abuso de alcohol y la ausencia de diagnóstico de estas patologías.…”
Section: Discussionunclassified
See 2 more Smart Citations